UTILIZATION OF MANGROVE PLANTS IN INCREASING THE INCOME OF TANJUNG REJO VILLAGE COMMUNITIES PERCUT SEI TUAN DISTRICT - Purnama Yanti Purba; Herlin Munthe; Rafida Khairani; Kristi Endah Ndilosa Ginting; Rudiyanto Rudiyanto (Jurnal Ekonomi, 2022)
The purpose of this study was to find out what types of mangroves are used as processed food in Tanjung Rejo Village, Percut Sei Tuan District, How much influence does the use of mangrove plants have on increasing the income of the Esa tanjung Rejo community and what solutions are given to the obstacles faced by the Tanjung Rejo Village community. This research uses primary and secondary data with descriptive analysis method. The results of this study indicate that there are 3 mangrove ingredients which are processed food ingredients for Tanjung Rejo village, namely api-api fruit to make jam and syrup, berembeng fruit to make mangrove dodol and jeruju leaves to make jeruju sticks and jeruju chips. Researchers have conducted training seminars on administration, accounting, HRM, marketing and digital marketing using a public understanding questionnaire. The solution provided is the renewal of traditional tools into more modern tools so that the processing results are effective in terms of time and labor and output.